The Role of Asaatidz in Developing an Interest in Memorizing the Quran in Santriwan With the Kulliyyatu Tahfiidzil Quran Program at the Assalaam Islamic Modern Boarding School Pebelan Kartasura Sukoharjo - Wahyudi Prabowo; Bambang Sumardjoko; Ari Anshori (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
The Quran has an important role in every human life because it is a reference and guide for all mankind as well as a guide in determining something that is right and vanity. The obligation of every human being is to be able to learn and understand the content in it. So the first step to be able and to understand the Quran is to read according to the rules of tajwid which is then continued by memorizing it. The purpose of this study is to know how the role of assatidz in developing interest in memorizing the Quran for santriwan with the Kulliyyatu Tahfiidzil Quran (KTQ) program at the Assalaam Islamic Modern Islamic Boarding School Sukoharjo. The method in this research is qualitative. And the sample is the santriwan member of KTQ. The conclusion of this study that the role of companion asaatidz is very important in the process of memorizing the Quran so that it can become a character of students in their daily lives. Educators must also carefully look at the development of students in memorizing the Quran correctly according to the rules of tajwid science and good role models or examples in words and actions in memorizing the Quran. The result of this research supports the research of Nurul Latifatul Inayati (2018).